Lithium iron tungstate modified PEO-based composite solid electrolyte and preparation method thereof, solid-state battery
Through the preparation of the PEO-based composite solid electrolyte modified with lithium iron tungstate, the problems of limited ion transport capability and poor crystallinity of the PEO-based electrolyte are solved, and the performance of the electrolyte and the service life of the battery are significantly improved.
Patent Information
- Application Number
- CN202411907065.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-24
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2044-12-24
AI Technical Summary
The existing PEO-based polymer solid electrolytes have problems such as limited ion transport capability and room temperature crystallization, which leads to shortening their service life and poor safety in lithium-ion batteries.
Lithium iron tungstate modified PEO-based composite solid electrolyte is used to prepare lithium iron tungstate material through ball mill mixing and sintering processes, and is mixed with PEO and lithium-based electrolyte in solid phase to form a composite electrolyte.
It effectively improves the ion transport performance and crystallinity of PEO-based solid electrolytes, improves the mechanical properties and density of the electrolytes, extends the service life of the battery and improves safety.
Smart Images

Figure CN119361802B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of solid electrolytes, and in particular relates to a lithium iron tungstate modified PEO-based composite solid electrolyte and a preparation method thereof, and a solid-state battery. Background Art
[0002] Commercial lithium-ion batteries generally use organic liquid electrolytes, but the energy density of lithium-ion batteries using organic liquid electrolytes is increased, and safety issues are prone to occur. In addition, lithium-ion batteries using organic liquid electrolytes also face the following problems: First, under high voltage and high oxidation activity conditions, the electrolyte is easily oxidized and decomposed; second, the SEI film continues to grow and consumes the electrolyte; third, there are serious problems with matching with the metal lithium negative electrode; the existence of these problems greatly shortens the service life of lithium-ion batteries. Solid-state batteries use solid electrolytes. The emergence of solid-state batteries is expected to solve the problems of short life and poor safety of existing liquid electrolyte batteries, and is expected to further improve the energy density of batteries.
[0003] At present, the solid electrolytes of solid-state batteries can be divided into two types: inorganic solid electrolytes and polymer solid electrolytes. Inorganic solid electrolytes such as sulfide solid electrolytes have a rigid interface and large interface resistance that is difficult to overcome. In addition, their preparation process is complex, the cost is high, and their application is difficult. Polymer solid electrolytes have inherent advantages in interface contact, good film forming properties and flexibility, and show good application prospects in flexible wearable electronic devices. Common polymer matrices for polymer solid electrolytes are polyethylene oxide (PEO), polyacrylonitrile (PAN), polyvinylidene fluoride (PVDF), polyvinyl pyrrolidone (PVP) and polymethyl methacrylate (PMMA). Among the many polymer-based solid electrolytes, PEO (polyethylene oxide)-based polymer solid electrolytes have the highest conductivity, and at the same time have the advantages of high safety, mechanical flexibility, viscoelasticity and easy film formation. They are considered to be one of the most promising solid electrolyte materials. However, PEO-based polymers have problems such as limited ion transmission capacity and room temperature crystallization. Therefore, improving the ion transmission capacity and improving the crystallinity of PEO-based polymer electrolytes are issues that need to be solved urgently. Summary of the invention
[0004] The purpose of the present invention is to provide a lithium iron tungstate modified PEO-based composite solid electrolyte and a preparation method thereof, and a solid-state battery, and to further improve the ion transport performance and crystallinity of the PEO-based composite solid electrolyte.
[0005] In the first aspect, the present invention provides a lithium iron tungstate modified PEO-based composite solid electrolyte, which adopts the following technical scheme:
[0006] A lithium iron tungstate modified PEO-based composite solid electrolyte, comprising: lithium iron tungstate, PEO and a lithium-based electrolyte, wherein: the structural formula of lithium iron tungstate is Li x Fe y W z O m , x:y:z is (2~5):(0.5~1.5):(1~4), and x+3y+6z=2m.
[0007] Preferably, the lithium iron tungstate is Li3FeW2O9, Li3FeW4O 15 , Li5FeWO7 or at least one of the following.
[0008] Preferably, the lithium-based electrolyte is one or more of LiPF6, LiTFSI, LiFSI, and LiBF4.
[0009] Preferably, the ratio of the mass of lithium iron tungstate to the total mass of PEO and lithium-based electrolyte is (1-10):100; the ratio of the molar number of repeating monomers in PEO to the molar number of lithium-based electrolyte is (15-20):1.
[0010] The structural formula of PEO is ; The repeating unit is OCH2CH2.
[0011] In a second aspect, the present invention provides a method for preparing a lithium iron tungstate modified PEO-based composite solid electrolyte, comprising the following steps:
[0012] The lithium iron tungstate, PEO and lithium-based electrolyte are ball-milled to obtain a mixed powder; a solvent is added to the mixed powder, and the mixed powder is ground and dispersed to obtain a slurry; the slurry is coated on a bottom plate, and after vacuum drying, a lithium iron tungstate modified PEO-based composite solid electrolyte is obtained.
[0013] Preferably, the preparation method of lithium iron tungstate comprises the following steps: mixing a tungsten source, an iron source and a lithium source by ball milling to obtain a mixed powder; and sintering the mixed powder to obtain a lithium iron tungstate material.
[0014] Preferably, the tungsten source, iron source and lithium source are added in corresponding proportions according to the molar ratio of tungsten, iron and lithium in the structural formula of lithium iron tungstate;
[0015] The tungsten source is one or more of tungsten trioxide, lithium tungstate, and ferrous tungstate;
[0016] The iron source is one or more of ferrous tungstate, ferroferric oxide, and ferrous oxide;
[0017] The lithium source is one or more of lithium oxide, lithium tungstate, lithium carbonate, lithium acetate and lithium oxalate.
[0018] Preferably, the sintering temperature is 800-1000° C., and the sintering time is 10-30 hours.
[0019] Preferably, the solvent is acetonitrile, tetrahydrofuran and N,N - one or more of dimethylformamide; the mass volume ratio of PEO to solvent is 1g: (10~30)mL;
[0020] Preferably, the vacuum drying temperature is 70-90° C., and the vacuum drying time is 6-12 h.
[0021] In a third aspect, the present invention provides a solid-state battery, the electrolyte of which adopts the aforementioned lithium iron tungstate modified PEO-based composite solid-state electrolyte.
[0022] The above one or more technical solutions of the present invention can achieve at least one of the following beneficial effects:
[0023] (1) Lithium iron tungstate is an inorganic ceramic material that contains lithium ions in its structure. Therefore, after being composite-modified with a PEO-based composite solid electrolyte, it can effectively improve the ion transport performance of the PEO-based solid electrolyte. In addition, the inorganic ceramic lithium iron tungstate powder material will reduce the crystallinity of the PEO polymer in the electrolyte, effectively improving the mechanical properties of the solid electrolyte. Furthermore, lithium iron tungstate, as a solid phase filler, can increase the density of the solid electrolyte membrane, thereby avoiding short circuits in the battery.
[0024] (2) The lithium iron tungstate used in the present invention contains tungstate, which has excellent structural stability and conductivity. In addition, the iron source in the lithium iron tungstate can achieve reversible redox, so that lithium ions can be reversibly deintercalated, further improving the ionic conductivity of the solid electrolyte.
[0025] (3) The preparation process of the present invention is simple, the process is short, the raw materials are easily available, no toxic or harmful substances are produced during the preparation process, and it is easy to achieve large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 This is a surface morphology SEM image of the lithium iron tungstate modified PEO-based composite solid electrolyte prepared in Example 1.
[0027] Figure 2 Electrochemical performance diagram of solid-state batteries assembled with modified PEO-based composite solid electrolytes prepared in Examples 1 to 7 and Comparative Examples 1 to 2. DETAILED DESCRIPTION
[0028] In order to facilitate the understanding of the present invention, the present invention will be described more comprehensively and meticulously below in conjunction with the accompanying drawings and preferred embodiments of the present invention, but the protection scope of the present invention is not limited to the following specific embodiments.
[0029] Unless otherwise defined, all the professional terms used below have the same meanings as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.
[0030] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.
[0031] The molecular weight range of PEO used in the embodiments of the present invention is 2,000,000-5,000,000.
[0032] Example 1
[0033] In the solid electrolyte of this embodiment: the structural formula of lithium iron tungstate is: Li3FeW2O9; the lithium-based electrolyte is LiTFSI; and the molecular weight of PEO is 3000000.
[0034] The specific preparation method is as follows:
[0035] (1) 26.2 g of lithium tungstate (Li2WO4), 30.4 g of ferrous tungstate (FeWO4) and 1.56 g of Li2O were mixed by ball milling to obtain a mixed powder; the mixed powder was placed in a muffle furnace and sintered at 930°C for 15 h to obtain Li3FeW2O9 material.
[0036] (2) 5 g of Li3FeW2O9 prepared in step (1) was solid-phase mixed with 100 g of the main components of the solid electrolyte PEO (73.4 g) and LiTFSI (26.6 g) to obtain a mixed powder, wherein the molar ratio of the repeating unit in PEO to LiTFSI was 18:1. 2 L of acetonitrile was dropped into the mixed powder, and the mixture was ground to obtain a slurry. The slurry was evenly coated on a polytetrafluoroethylene plate (coating thickness was 0.2 mm), and vacuum dried at 80°C for 8 h to obtain a lithium iron tungstate modified PEO-based composite solid electrolyte.
[0037] The surface morphology SEM image of the lithium iron tungstate modified PEO-based composite solid electrolyte prepared in this example is as follows: Figure 1 As shown, it can be seen that the surface of the lithium iron tungstate modified PEO-based composite solid electrolyte is relatively uniform, the thickness is consistent, and there is no obvious granular accumulation, indicating that the distribution of each component in the composite solid electrolyte is relatively uniform and the composite effect is better.
[0038] Comparative Example 1
[0039] In the solid electrolyte of this comparative example: lithium tungstate (Li2WO4) is used for modification, and the other components are the same as those in Example 1.
[0040] Its preparation method is:
[0041] 5gLi2WO4 was ball-milled with 100g of the main components of the solid electrolyte, PEO (73.4g) and LiTFSI (26.6g), to obtain a mixed powder, wherein the molar ratio of the repeating monomer in PEO to LiTFSI was 18:1. 2L of acetonitrile was dropped into the mixed powder, and the mixture was ground to obtain a slurry. The slurry was evenly coated on a polytetrafluoroethylene plate (coating thickness was 0.22mm), and after vacuum drying at 80°C for 8h, a lithium tungstate-modified PEO-based composite solid electrolyte was obtained.
[0042] Comparative Example 2
[0043] In the solid electrolyte of this comparative example: lithium ferrite (LiFeO2) is used for modification, and the other components are the same as those in Example 1.
[0044] Its preparation method is:
[0045] 5gLiFeO2 was ball-milled with 100g of the main components of the solid electrolyte, PEO (73.4g) and LiTFSI (26.6g), to obtain a mixed powder, wherein the molar ratio of the repeating monomer in PEO to LiTFSI was 18:1. 2L of acetonitrile was dropped into the mixed powder, and the mixture was ground to obtain a slurry. The slurry was evenly coated on a polytetrafluoroethylene plate (coating thickness was 0.22mm), and after vacuum drying at 80°C for 8h, a lithium ferrite-modified PEO-based composite solid electrolyte was obtained.
[0046] Example 2
[0047] In the solid electrolyte of this embodiment, the structural formula of lithium iron tungstate is: Li3FeW4O 15 ; The lithium-based electrolyte is LiTFSI; the molecular weight of PEO is 3000000.
[0048] (1) 69.6 g of tungsten trioxide (WO3), 30.4 g of ferrous tungstate (FeWO4) and 19.8 g of CH3COOLi were mixed by ball milling to obtain a mixed powder; the mixed powder was placed in a muffle furnace and sintered at 930 °C for 15 h to obtain Li3FeW4O 15 Material.
[0049] (2) 5 g of Li3FeW4O prepared in step (1) 15Solid phase mixing with 100g of solid electrolyte main components PEO (73.4) and LiTFSI (26.6g) to obtain a mixed powder, wherein the molar ratio of PEO to LiTFSI is 18:1. 2L of acetonitrile is dropped into the mixed powder, and the mixture is ground to be evenly dispersed to obtain a slurry. The slurry is evenly coated on a polytetrafluoroethylene plate (coating thickness is 0.22mm), and vacuum dried at 80°C for 8h to obtain a lithium iron tungstate modified PEO-based composite solid electrolyte.
[0050] Example 3
[0051] In the solid electrolyte of this embodiment: the structural formula of lithium iron tungstate is: Li5FeWO7; the lithium-based electrolyte is LiTFSI; and the molecular weight of PEO is 3,000,000.
[0052] (1) 52.4 g of lithium tungstate (Li2WO4), 16 g of iron oxide (Fe2O3) and 1.56 g of Li2O were mixed by ball milling to obtain a mixed powder; the mixed powder was placed in a muffle furnace and sintered at 930°C for 15 h to obtain Li5FeWO7 material.
[0053] (2) 5 g of Li5FeWO7 prepared in step (1) was solid-phase mixed with 100 g of the main components of the solid electrolyte PEO (73.4 g) and LiTFSI (26.6 g) to obtain a mixed powder, wherein the molar ratio of PEO to LiTFSI was 18:1. 2 L of acetonitrile was dropped into the mixed powder, and the mixture was ground to obtain a slurry. The slurry was evenly coated on a polytetrafluoroethylene plate (coating thickness was 0.22 mm), and vacuum dried at 80 ° C for 8 h to obtain a lithium iron tungstate modified PEO-based composite solid electrolyte.
[0054] Example 4
[0055] The process is basically the same as Example 1, except that the amount of Li3FeW2O9 added in step (2) is 1 g.
[0056] Example 5
[0057] The process is basically the same as Example 1, except that the amount of Li3FeW2O9 added in step (2) is 10 g.
[0058] Example 6
[0059] In the solid electrolyte of this embodiment: the structural formula of lithium iron tungstate is: Li3FeW2O9; the lithium-based electrolyte is LiPF6; and the molecular weight of PEO is 2000000.
[0060] The specific preparation method is as follows:
[0061] (1) 26.2 g of lithium tungstate (Li2WO4), 30.4 g of ferrous tungstate (FeWO4) and 1.56 g of Li2O were mixed by ball milling to obtain a mixed powder; the mixed powder was placed in a muffle furnace and sintered at 800°C for 24 h to obtain Li3FeW2O9 material.
[0062] (2) 4 g of Li3FeW2O9 prepared in step (1) was mixed with 100 g of the main components of the solid electrolyte, PEO (81.3 g) and LiPF6 (18.7 g), to obtain a mixed powder, wherein the molar ratio of PEO to LiPF6 was 15:1. 1 L of N,N -dimethylformamide, grind to make it uniformly dispersed to obtain slurry. The slurry is evenly coated on a polytetrafluoroethylene plate (coating thickness is 0.25 mm), and vacuum dried at 70°C for 12 hours to obtain a lithium iron tungstate modified PEO-based composite solid electrolyte.
[0063] Example 7
[0064] In the solid electrolyte of this embodiment: the structural formula of lithium iron tungstate is: Li3FeW2O9; the lithium-based electrolyte is LiBF4; and the molecular weight of PEO is 5000000.
[0065] The specific preparation method is as follows:
[0066] (1) 26.2 g of lithium tungstate (Li2WO4), 30.4 g of ferrous tungstate (FeWO4) and 1.56 g of Li2O were mixed by ball milling to obtain a mixed powder; the mixed powder was placed in a muffle furnace and sintered at 1000°C for 10 h to obtain Li3FeW2O9 material.
[0067] (2) 8 g of Li3FeW2O9 prepared in step (1) was solid-phase mixed with 100 g of the main components of the solid electrolyte PEO (90.4 g) and LiBF4 (9.6 g) to obtain a mixed powder, wherein the molar ratio of PEO to LiBF4 was 20:1. 2.5 L of tetrahydrofuran was dripped into the mixed powder, and the mixture was ground to be uniformly dispersed to obtain a slurry. The slurry was evenly coated on a polytetrafluoroethylene plate (coating thickness was 0.24 mm), and vacuum dried at 90°C for 7 h to obtain a lithium iron tungstate modified PEO-based composite solid electrolyte.
[0068] Solid-state battery assembly is accomplished by:
[0069] The modified PEO-based composite solid electrolyte membrane prepared in Examples 1 to 7 and Comparative Examples 1 to 2 was cut into 18 mm diameter discs as electrolyte membranes, lithium sheets were used as negative electrodes, and LiFePO4 was used as positive electrode materials to prepare positive electrode sheets; the positive electrode sheets, electrolyte membrane sheets and lithium sheets were assembled into CR2032 button batteries in a glove box. Wherein: the method for preparing LiFePO4 as a positive electrode material into a positive electrode sheet is: mixing LiFePO4: acetylene black: PVDF in a mass ratio of 8:1:1, using N-methylpyrrolidone (NMP) as a solvent, placing the mixture in a small beaker at a speed of 800 r / min and stirring the mixture for 2 hours to obtain a slurry; using an automatic coating machine to coat the slurry on a current collector aluminum foil, placing it flat on a tempered glass and transferring it to a vacuum drying oven at 85°C for drying for 4 hours, punching the sheet into a positive electrode sheet with a diameter of 12 mm, and then drying it in a vacuum drying oven at 105°C for 4 hours.
[0070] After the battery was assembled and aged for 12 hours, it was activated for 3 cycles at a voltage of 2.5~4.3V and a current density of 0.1C, and then cycled for 100 cycles at a current density of 1C.
[0071] The data graphs of the cycle stability and discharge specific capacity of the solid-state batteries prepared by the composite solid electrolytes prepared in Examples 1 to 7 of the present invention and Comparative Examples 1 to 2 are as follows: Figure 2 shown.
[0072] As can be seen from the figure, the cycle stability and discharge capacity ratio of the solid-state battery assembled with the lithium iron tungstate modified PEO-based composite solid electrolyte prepared in Example 1 are significantly better than those of the solid-state battery assembled with the lithium tungstate modified PEO-based composite solid electrolyte in Comparative Example 1 and the lithium ferrite modified PEO-based composite solid electrolyte in Comparative Example 2; this indicates that the modification of lithium iron tungstate can significantly improve the electrochemical properties of the solid-state electrolyte.
[0073] In Examples 1 to 3, lithium iron tungstate with different element ratios was used to modify the PEO-based composite solid electrolyte. The cycle stability and discharge capacity of the solid-state batteries assembled therefrom had performance fluctuations to a certain extent, but all had good cycle stability and discharge specific capacity.
[0074] Example 1, Example 4 and Example 5 mainly change the amount of lithium iron tungstate added. The cycle stability and discharge capacity of the solid-state battery assembled with different added amounts of lithium iron tungstate modified PEO-based composite solid electrolyte will fluctuate to a certain extent. Overall, the performance of Example 1 is optimal when the amount of lithium iron tungstate added is 5wt%.
[0075] The main differences between Example 6 and Example 7 are that there are certain changes in the preparation process and addition ratio of the lithium iron tungstate modified PEO-based composite solid electrolyte. The cycle stability and discharge capacity of the assembled solid-state batteries will also fluctuate to a certain extent, but both have good cycle stability and discharge specific capacity.
[0076] The above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with the technology to understand the content of the present invention and implement it accordingly, and they cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.
Claims
1. A lithium iron tungstate modified PEO-based composite solid electrolyte, characterized in that: The components include: lithium iron tungstate, PEO and lithium-based electrolyte, among which: lithium iron tungstate is Li3FeW2O9, Li3FeW4O 15 , Li5FeWO7 or at least one of the following.
2. The lithium iron tungstate modified PEO-based composite solid electrolyte according to claim 1, characterized in that: The lithium-based electrolyte is one or more of LiPF6, LiTFSI, LiFSI, and LiBF4.
3. The lithium iron tungstate modified PEO-based composite solid electrolyte according to any one of claims 1 to 2, characterized in that: The ratio of the mass of lithium iron tungstate to the total mass of PEO and the lithium-based electrolyte is (1-10):100; the ratio of the molar number of repeating units in PEO to the molar number of the lithium-based electrolyte is (15-20):
1.
4. A method for preparing a lithium iron tungstate modified PEO-based composite solid electrolyte according to any one of claims 1 to 3, characterized in that: The following steps are involved: The lithium iron tungstate, PEO and lithium-based electrolyte are ball-milled to obtain a mixed powder; a solvent is added to the mixed powder, and the mixed powder is ground and dispersed to obtain a slurry; the slurry is coated on a bottom plate, and after vacuum drying, a lithium iron tungstate modified PEO-based composite solid electrolyte is obtained.
5. The method for preparing the lithium iron tungstate modified PEO-based composite solid electrolyte according to claim 4, characterized in that: The preparation method of lithium iron tungstate comprises the following steps: mixing a tungsten source, an iron source and a lithium source by ball milling to obtain a mixed powder; and sintering the mixed powder to obtain lithium iron tungstate.
6. The method for preparing the lithium iron tungstate modified PEO-based composite solid electrolyte according to claim 5, characterized in that: The tungsten source, iron source and lithium source are added in corresponding proportions according to the molar ratio of tungsten, iron and lithium in the structural formula of lithium iron tungstate; The tungsten source is one or more of tungsten trioxide, lithium tungstate, and ferrous tungstate; The iron source is one or more of ferrous tungstate, ferroferric oxide, and ferrous oxide; The lithium source is one or more of lithium oxide, lithium tungstate, lithium carbonate, lithium acetate and lithium oxalate.
7. The method for preparing the lithium iron tungstate modified PEO-based composite solid electrolyte according to claim 4, characterized in that: The solvent is one or more of acetonitrile, tetrahydrofuran and N,N-dimethylformamide; the mass volume ratio of PEO to the solvent is 1g:(10-30)mL.
8. The method for preparing the lithium iron tungstate modified PEO-based composite solid electrolyte according to claim 4, characterized in that: The vacuum drying temperature is 70-90° C., and the vacuum drying time is 6-12 hours.
9. A solid-state battery, characterized in that: The electrolyte membrane adopts the lithium iron tungstate modified PEO-based composite solid electrolyte described in any one of claims 1 to 3.
Citation Information
Patent Citations
FeLiWO4 anode film material and its making method
CN101034740A
SnO2 / iron lithium tungstate / carbon composite nano material and preparation method thereof
CN106067548A